Fourier transform-infrared photoacoustic spectroscopy applied in fish scales to access environmental integrity: A case study of Astyanax altiparanae species - Santana, C. A.; Andrade, L. H. C.; Suarez, Y. R.; Yukimitu, K. [UNESP]; Moraes, J. C. S. [UNESP]; Lima, S. M. (Elsevier B.V., 2015)
Fish scales have been used to differentiate fish species and to give information on water pollution, besides others different purposes. In the present work, we are proposing, for the first time to our knowledge, to available the absorption from fish scales with Fourier Transform Infrared Photoacoustic Spectroscopy (FTIR-PAS) to assess the environmental integrity of different habitats. The infrared absorption measurements were performed directly on fish scales from the Astyanax altiparanae species, in order to check if the scales, and consequently the species, can be used as environmental bioindicator. The main absorption intensities were used as variables in the multivariate statistical analysis. It was noted that the chemical composition of the scales is directly related to the available food in the habitats, which is related to the integrity level of the environmental. The results point the fish scales as bioindicator to be applied with FTIR-PAS for monitoring aquatic ecosystems. (c) 2015 Elsevier B.V. All rights reserved.
Keywords: Bioindicators; Chemical vibrational modes; Fish collagen; Mid-infrared absorption spectroscopy; Multivariate statistical analysis